Gambaran Tingkat Pengetahuan Bantuan Hidup Dasar Mahasiswa Olahraga Undiksha - Mahendrayani, Luh Ita; Made Ririn Sri Wulandari; Ni Kadek Diah Purnamayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to identify and describe the level of BLS knowledge among sports students at Universitas Pendidikan Ganesha (Undiksha). This research employed a descriptive design using a total sampling technique involving 120 sports student respondents. Data were collected in April 2026 using a validated questionnaire consisting of 18 items distributed via Google Forms and analyzed using descriptive statistics. The results showed that the respondents’ level of knowledge was categorized as very good, with 79.2% of respondents achieving this category. The study concludes that Undiksha sports students possess a very strong cognitive understanding of BLS principles and procedures, supported by their productive age and academic background, which is sensitive to injury risks. It is recommended that institutions integrate regular practical training to maintain this emergency preparedness. Keywords: Basic Life Support, Sports Students, Knowledge.